PENGARUH MODEL NHT PADA PEMBELAJARAN IPA TERHADAP HASIL BELAJAR SISWA KELAS V SEKOLAH DASAR - Afriyanti, Afriyanti; Kresnadi, Hery; Sugiyono, Sugiyono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to analyze the effect of the application of number head together on the results of learning in learning natural sciences of class V students of Pontianak Utara 38 Elementary School. The method used is the experimental method, while the form of research used is quasi experimental design with nonequivalent control group design. The population and sample in this study were all fifth grade students of Pontianak Utara 38 Elementary School. The data collection tool used was a multiple choice test with 45 questions. Based on data analysis, the average post-test results of the experimental class were 77,89 while the average post-test results of the control class were 75,36. The results of the t test are obtained tcount of 2,189 and t table Î± = 5% (with dk = 20 + 23 - 2 = 41) of 2,020, which means tcount (2,189)> t table (2,020), then the alternative hypothesis (Ha) is accepted. It can be concluded that there is influence the application of number head together on the results of learning in learning natural sciences of class V students of Pontianak Utara 38 Elementary School.. From the results of the calculation of the effect size (ES) ES obtained is 0,4943 (small criteria). This means that the application of number head together have a good influence on the results of learning of learning in learning natural sciences of class V students of Pontianak Utara 38 Elementary School.Â Keywords: The Effect, Number Head Together, The Result Of Learning, Natural Science